Sentidos da esperança de usuários de serviços especializados em saúde mental durante a pandemia da Covid-19 - Pereira, Sarah Salvador (2024)
Introduction: Hope is a dimension that makes up human life, fundamental in the process of facing complex situations. The COVID-19 pandemic context can interfere with the hope process of people using specialized mental health services. It is believed that hope was even more compromised in the perception of users of specialized mental health services, due to factors of social isolation, changes in daily routine, difficulty in accessing the care offered by mental health services, changes in the scope of work, doubts and uncertainties regarding the COVID-19 disease. Objective: To analyze the meanings of hope in the speeches of users of specialized mental health services in a city in the interior of Minas Gerais in the context of the COVID-19 pandemic. Materials and Methods: Qualitative study based on the theoretical and methodological framework of French-based Discourse Analysis (DA) and the theoretical construct of Dufault and Martocchio's Model of Hope. The research involved four specialized mental health services: Psychosocial Care Center for Alcohol and Drugs (CAPS ad), Psychosocial Care Center II, Multiprofessional Mental Health Center and Post-covid Mental Health Care Center belonging to a city in the interior of Minas Gerais. Semi-structured interviews were conducted with 14 users of specialized Mental Health services from August 2022 to May 2023. Discourse analysis devices were used to analyze the data. To analyze the data, the devices Interdiscourse, Metaphor and Paraphrase of Discourse Analysis were used. Results and Discussion: 14 interviews were carried out with users of specialized mental health services, 5 users of the Multiprofessional Mental Health Center, 4 users of CAPS II, 3 users of CAPS Ad and 2 users of the Post-COVID Mental Health Care Center. Of these 14 subjects, 10 were female and 4 were male. The discourse analysis process enabled the elaboration of two discursive blocks: 1) The meanings of Hope constructed in the COVID-19 Pandemic and 2) Experiences during the COVID-19 pandemic – What inhibits or promotes hope? The discursive block entitled “The meanings of Hope constructed in the COVID-19 Pandemic” addresses the meanings constructed about hope that are permeated by the effects arising from discursive memories. The discursive excerpts enunciate signs of religious discourse; solidarity speech; disease model. and overcoming speech. The discursive block entitled “Experiences during the COVID-19 pandemic – What inhibits or promotes hope?” explored life circumstances and experiences lived by the subjects that affected the production of meanings about hope in the pandemic context, which highlight the broad and strict production conditions in which the speeches were enunciated. The COVID-19 pandemic period was marked by experiences of grief, indifference, intensification of social injustices, fear and finding support within the family. Final Considerations: The COVID-19 pandemic influenced the construction of meanings about hope among users of specialized mental health services and generated consequences for people's mental health. It is believed to be important to enable health professionals, especially nurses, who work in CAPS and CAPS ad to understand the constructed meanings of hope and recognize it as a therapeutic resource that constitutes care. The importance of recognizing the promotion of hope as an intervention in clinical and care practice is highlighted.